2021
DOI: 10.3126/paj.v4i0.37005
|View full text |Cite
|
Sign up to set email alerts
|

Association between Handwashing Knowledge and Practices among the Students in Nepal

Abstract: Regular handwashing with soap and running water is one of the effective ways to stop spreading of germs that protects us from the disease. The aim of this study is to assess the handwashing knowledge and practice among the selected school students of Bardiya district in Nepal. To address this objective, the school-based descriptive cross-sectional design was applied. A total of 327 students including 9 to 12 grades were taken from four secondary schools using the multistage sampling technique. The validated se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, a study by Sharma in 2021 among secondary-level students in Nepal found that 94.8 percent of respondents washed their hands with soap before eating. Similarly, 90.7 percent in the study area washed their hands after defecation, whereas in the same study, only 84.1 percent washed their hands with soap and water [13].…”
Section: Discussionmentioning
confidence: 55%
“…However, a study by Sharma in 2021 among secondary-level students in Nepal found that 94.8 percent of respondents washed their hands with soap before eating. Similarly, 90.7 percent in the study area washed their hands after defecation, whereas in the same study, only 84.1 percent washed their hands with soap and water [13].…”
Section: Discussionmentioning
confidence: 55%
“…The sample size was calculated using the standard statistical formula presented by Yamane, 1967 14 S = boldz 2 × p × ( 1 p ) bolde 2 for the infinite population. The procedure which was used to compute the sample size is presented in appendix section (see Appendix A).…”
Section: Methodsmentioning
confidence: 99%
“…for an infinite population (Sharma et al, 2021). So, the calculated sample size was 384; however, to make a more representative sample and minimize sampling errors , the calculated sample size was multiplied by the design effect of two.…”
Section: Sample Size and Sampling Techniquesmentioning
confidence: 99%